Natural Regeneration Population of Batang Rattan (Calamus zollingeri Beccari) in Nupabomba Village, Production Forest Area, Central Sulawesi - Titi Kalima; Diana Prameswari (Institut Pertanian Bogor (IPB University), 2018)
This research aimed to obtain information on the abundance and natural regeneration population of Calamus zollingeri Beccari and identify dominant trees in the site. The study used the descriptive method with a survey technique. A transect of 520 m consisting of 13 plots of 20 × 20 m was established. The number of individuals, the lengths, and diameters of the stems for the seedlings, young, semi-mature, and mature cutting rattan were recorded along with the surrounding vegetation. Relative density, the frequency of rattan plants and trees were summed to obtain the important value index (IVI) of each growth rate. The results showed that the natural regeneration population was quite abundant, i.e. 738.46, 296.15, 132.69, and 25.00 stems ha-1 for seedlings, young, semi-mature, and mature rattan, respectively as a response to logging in which a number of the seedlings tended to increase after logging. The trees associated with C. zollingeri were Baccaurea rasemosa, Celtis philippensis, and Fagraea fragrans. The existence of seedling regeneration is a guarantee to the sustainability of C. zollingeri in the future. Therefore, forests with rattan need to be developed to improve the preservation, utilization, and conservation of its genetic resources, as well as enhancing the community awareness